Cultural encounters with the Arabian Nights in nineteenth-century Britain - Dickson, Melissa (Of University of Birmingham) (Edinburgh critical studies in Victorian culture., 2019)
Aladdin, Sinbad, Ali Baba and the Forty Thieves, Scheherazade winding out her intricate tales to win her nightly stay of execution: the stories of the Arabian Nights are a familiar and much-loved part of the English literary inheritance. But how did these tales become so much a part of the British cultural landscape? This book identifies the nineteenth century as the beginning of the large-scale absorption of the Arabian Nights into British literature and culture. It explores how this period used the stories as a means of articulating its own experiences of a rapidly changing environment. It also argues for a view of the tales not as a depiction of otherness, but as a site of recognition and imaginative exchange between East and West, in a period when such common ground was rarely found.